Distinct Kinase-Independent Role of RIPK3 in CD11c(+) Mononuclear Phagocytes in Cytokine-Induced Tissue Repair - Moriwaki, Kenta (Cell Rep, 2017)
Receptor interacting protein kinase 3 (RIPK3) induces necroptosis, a type of regulated necrosis, through its kinase domain and RIP homotypic interaction motif (RHIM). In addition, RIPK3 has been shown to regulate NLRP3 inflammasome and NF-κB activation. However, the relative contribution of these signaling pathways to RIPK3-dependent inflammation in distinct immune effectors is unknown. To interrogate these questions, we generated RIPK3-GFP reporter mice. We found that colonic CD11c(+)CD11b(+)CD14(+) mononuclear phagocytes (MNPs) expressed the highest level of RIPK3 in the lamina propria. Consequently, deletion of the RIPK3 RHIM in CD11c(+) cells alone was sufficient to impair DSS-induced IL-23 and IL-1β expression, leading to severe intestinal inflammation. In contrast, mice expressing kinase inactive RIPK3 were not hypersensitive to DSS. Thus, a key physiological function of RIPK3 is to promote reparative cytokine expression through intestinal CD11c(+) MNPs in a kinase- and necroptosis-independent manner.